Family Resilience Factors in Long-Distance Marriage Couples in Indonesia: A Systematic Literature Review - Mubarok, Ali Syahidin; Agustina, Mirna Wahyu; Diningrum, Nahda Tarisa; Syifa, Nadia; Zeirliana, Elmalia Dwi (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
This study aims to identify and analyze factors influencing family resilience in long-distance marriages (LDM) in Indonesia through a systematic literature review approach. Family resilience in the context of LDM is essential to maintaining family harmony and stability despite limited physical interaction. This research method uses literature searches from various academic databases using publish or perish software with a publication period between 2019 and 2024. Inclusion criteria were determined to filter relevant articles focusing on LDM in Indonesia and family resilience. The analysis was carried out by classifying factors that influence family resilience and the causes of long-distance marriages that they must do. The study results showed that several dominant factors in increasing family resilience in LDM couples in Indonesia were effective communication, social support from the extended family and community, and higher levels of individual psychological well-being. Communication through digital media allows couples to maintain emotional closeness and overcome loneliness. Social support from extended family provides the practical and emotional assistance that couples need, while psychological well-being helps manage stress and increase individual resilience to long-distance challenges. Conflict management also contributes to creating family resilience. The dominant factors that cause long-distance marriages are career, financial inability, and limited employment opportunities around origin. This study concludes that communication factors, social support, and psychological well-being influence family resilience in LDM in Indonesia. This study suggests the need for community-based interventions and communication training for LDM couples to improve family resilience.